Faktor-faktor yang Mempengaruhi Kepatuhan Minum Obat Antiretroviral (Arv) pada Pasien Hiv-Aids: Literature Review - Zulkarnain, Zulkarnain; Huda, Nurul; Wahyuni, Sri (Jurnal Ners, 2025)
Introduction: HIV-AIDS is a disease for which a definitive cure has not yet been discovered. However, antiretroviral (ARV) therapy has proven to be highly effective in delaying the progression of HIV to AIDS by stimulating antibody production and triggering pro-inflammatory agents that suppress the viral load in the bloodstream, thereby significantly slowing down immune system deterioration. Objective: To identify the factors that influence adherence to antiretroviral (ARV) medication among patients living with HIV-AIDS. Methods: The literature search was conducted using databases such as Google Scholar, PubMed, ScienceDirect, ResearchGate, and Elsevier. The keywords used were “medication adherence,” “antiretroviral (ARV),” and “HIV-AIDS.” A total of seven relevant articles were identified. The selection process applied the PICO elements and the CRAAP evaluation method. Results: The findings indicate that factors influencing ARV medication adherence among HIV-AIDS patients include gender, age, education level, socioeconomic status, alcohol consumption and drug use habits, accessibility and trust in healthcare facilities, stigma, marital status, and family support. Conclusion: This study is expected to provide a significant contribution to understanding the factors affecting ARV medication adherence among HIV-AIDS patients and to support the development of nursing science.